Characterization of Biobased Alginate/Glycerol/ Sunflower Oil as Biodegradable Packaging - Dewi Maula Yasinta; Husni Amir (E3S Web of Conferences, 2020)
The most used packaging material was plastic, but can cause environmental problems because it was not easily degraded. Therefore, it was necessary to look for alternative packaging materials that are easily biodegraded including edible film. The main raw materials for edible films were alginates and plasticizers including glycerol and sunflower oil. The objective of this study was to determine the characteristics of edible film composed of alginate, glycerol and sunflower oil. The study was carried out through the manufacture of edible films composed of various alginates concentrations (2, 3, 4, 5 and 6%), 10% glycerol and 0.01% sunflower oil. The characteristics tested included thickness, tensile strength, elongation, solubility, and rate of water vapor transmission. The results showed that all treatments met the edible film standard of the Japanese Industrial Standard. The various alginate concentrations used did not significantly influence the water vapor transmission rate and tensile strength but significantly affected the elongation, solubility and thickness of the edible film.